Hubungan antara Penurunan Bobot Badan dan Peningkatan Produksi Ayam Petelur (Dekalb - Achmad, Razak; Sukra, Yuhara; -, Barizi; P Sinurat, Arnold (Jurnal Veteriner, 2010)
The aim of the research is to study the correlation between the decreased of body weight asand the increase of egg production, after the forced molting stress program. As many as 180medium type chickens, strain Dekalb Warren, aged 84 weeks old were used. The desain applied2x2x2 factorial and used complete randomized design in 5 times replications each of whichconsisted 4 chickens. The first factors were water supply and without water supply. The secondfactor was the duration of no feeding for 10 and 5 days. The third factor was the amount of feedgiven during recovery period, that was 50% and 25% of the normal consumption. The total of thetreatment of forced molting program applied were 9 treatments. The data obtained were analysedusing analysis of variance (anova), orthogonal comparison test and regression analysis. Theperformance and the mortality were also observed. The result showed that the treatment couldincreased egg production significantly and repaired layer performance with low mortality. It istherefore concluded that the increase of the egg production had no correlation with the decreaseof body weight in forced molting program.
Keywords: Body weight, Forced molting stress program, Egg production.